Determination of Acetyl Salicylic Acid in Aspirin Tablets Using the Volumetric Method - Boujwod, Firuze; Salema AL-Mansour; Hajar Bouhwih; Mashallah Almalki (AlQalam Journal of Medical and Applied Sciences, 2026)
Drug analysis plays a vital role in ensuring the quality and effectiveness of pharmaceutical products by determining the concentration of active ingredients. This study investigates the use of direct titration for the quantification of acetylsalicylic acid (ASA) in commercially available aspirin tablets. The research aimed to evaluate direct titration as a simple, economical, and practical method for routine pharmaceutical quality control in Darna City. Aspirin samples were collected from various neighborhood pharmacies supplying medications to local consumers. The concentration of ASA was determined using titrimetric analysis, and the results were compared across different commercial brands. The method demonstrated good precision and operational simplicity, making it suitable for routine analysis. However, limitations in accuracy were observed. The findings revealed variations in ASA content among the tested brands. Although most samples complied with official pharmacopeial standards, the observed differences indicate the need for continued monitoring to ensure consistency and therapeutic effectiveness. This study highlights the importance of improving manufacturing processes and refining analytical methods to strengthen pharmaceutical quality control and maintain drug reliability.